Alternative complement pathway hemolytic assays reveal incomplete complement blockade in patients treated with eculizumab - Puissant-Lubrano, Bénédicte (Clinical immunology (Orlando, Fla.), 2017)
Copyright © 2017 Elsevier Inc. All rights reserved.